A study of the discipline system construction of sports management and developmental trends in China - Qin, M. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The discipline system of China's sports management is still developing. With the development of modern sports and the reform of China`s sports management system, the discipline system of sports management requires further improvement. Based on an analysis of the existing discipline system construct for sports management and the current situation, this paper preliminarily discusses its framework and development trends.